Pengaruh Pemanfaatan Internet sebagai Sumber Belajar dan Perpustakaan Digital terhadap Prestasi Belajar Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret Surakarta - Dwi Widya Karunia; Sudarno Sudarno; Dini Octoria (Journal on Education, 2024)
This research aims to determine (1) the influence of using the internet on the learning achievement of Economic Education students at Sebelas Maret University, Surakarta (2) determine the effect of using digital libraries on the learning achievement of Economic Education students at Sebelas Maret University (3) determine the influence of using the internet as a learning and library resource digital simultaneously on the learning achievements of Sebelas Maret University Economic Education students. This research uses a quantitative descriptive type of research with a population of 352 Economic Education students class 20, 21, and 22. And sample set at 200 samples was taken using proportional random sampling. The data collection technique uses a questionnaire and was processed using SPSS 25. The result of research prove that (1) the use of the internet as a learning resource has a positive effect on the learning achievement of Economic Education students at Sebelas Maret University (2) the use of digital libraries has a positive effect on the learning achievement of Economic Education students at Sebelas Maret University (3) the use of the internet as a resource learning and digital libraries jointly influence the learning achievement of Economics Education students at Sebelas Maret University, Surakarta.